Strategi untuk Meningkatkan Prestasi Bagi Mahasiswa Underachiever - Nangoi Priscilla Francis (Bina Nusantara University, 2010)
Underachiever students are a group of students that are existed in our surrounding. The purpose of parents, teachers, and people in general are to develop a nation. Underachiever students have chances to be this nation’s breadwinner. They will need help from other people, in the right way and time. Main factors that influenced underachievers are motivation and emotional problems. Strategies needed are no farer than these main factors, but there should be more preparations.